A morphophonological approach to clipping in English - Denis Jamet (Lexis: Journal in English Lexicology, 2009)
In this paper, I will endeavor to define clipping, and see if there are any semantic differences between the multiplicity of terms: “shortening”, “clipping”, “truncations”, etc. I will examine the semantic role of clipping, and try to answer the following question: is clipping a word-formation device? I will mainly focus on the consequences and phonological realizations of clipping in English to show that the phonological regularities in the formation of clipping make it a potential word-formation device, by shedding new light on the tendencies formalizing the study of clipping.